Histopathological Pattern of Surgically Treated Thyroid Diseases - Aiad Abdullah Abdulrazak (Institute of Medico-legal Publications Pvt Ltd, 2021)
Background: Thyroid diseases are quite common and clinically important not only because they affectthe functions of other organs but also since most cases are eminently treatable. The incidence of thyroiddiseases varies from one geographical region to another. he present study was carried out to identify thehistopathological pattern of surgically treated thyroid disease in our setup and their frequency in relation toage and sex of the patients and to compare our findings with similar works in Iraq and globally.Materials and Methods: Total of 97 thyroidectomy case from Tikrit provine, Iraqwere included in thisstudy. Clinical, gross, and histopathological data were reviewed and analyzed.Results: Most of thyroid lesions were encountered at the age of 31-40 years. The most common thyroidlesion is multinodular goiter (40.21%). All thyroid diseases were more common in women than in menwith a male to female ratio of 1:5.93. Neoplastic lesions were found in 12.37% of cases (7.22% follicularadenoma; 5.15% thyroid carcinoma).Conclusion: Results of this study are comparable with several studies on thyroid diseases in other areasof Iraq and globally. Multinodular goiter need to be prevented by appropriate measures since Multinodulargoiter of prolonged duration in iodine deficient areas poses a risk factor for the development of follicularcarcinoma.